Racializing Experiences of Foreign-Born and Ethnically Diverse Black Male Engineering Graduate Students: Implications for Student Affairs Practice, Policy, and Research - Burt, Brian A.; Knight, Alexander; Roberson, Justin (Journal of International Students, 2017)
Despite a growing body of work on the experiences of Black collegians, the higher education knowledge base lacks scholarship focused on Black men in graduate programs who are foreign-born and/or identify ethnically as other than African American. In this article, we provide a domain-specific investigation (i.e., based on students’ field of study), centering on nine Black men in engineering graduate programs. Three themes emerged regarding students’ racialized experiences and effects of racialization: (1) racialization as a transitional process; (2) cultural identity (dis)integrity; and (3) racialized imposter syndrome. We conclude with implications for developing and implementing promising practices and activities that aid students throughout graduate school. Such targeted efforts might also improve the likelihood of students remaining in the engineering workforce.